FREQUENCY OF POLYMORPHISM OF ALA16VAL GENE SOD2 IN SAMPLES OF MONGOLOID AND CAUCASOID POPULATION, LIVING IN EASTERN SIBERIA - L. I. Kolesnikova; T. A. Bairova; O. A. Pervushina (Acta Biomedica Scientifica)
The article presents the study of superoxide dismutase 2 gene polymorphism that plays an important role in antioxidant protection of an organism. We performed genetic typing in representatives of two ethnic groups of Eastern Siberia - Buryats (Mongoloid) and Russians (Caucasoid). Alleles frequencies among Russians were Ala = 0,492; Val = 0,508; among Buryats Ala = 0,343; Val = 0,657. We compared these frequencies between the populations from Russia and from abroad (according to the results of other researches).